If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (6x + -9) + (4x + 7) = 118 Reorder the terms: (-9 + 6x) + (4x + 7) = 118 Remove parenthesis around (-9 + 6x) -9 + 6x + (4x + 7) = 118 Reorder the terms: -9 + 6x + (7 + 4x) = 118 Remove parenthesis around (7 + 4x) -9 + 6x + 7 + 4x = 118 Reorder the terms: -9 + 7 + 6x + 4x = 118 Combine like terms: -9 + 7 = -2 -2 + 6x + 4x = 118 Combine like terms: 6x + 4x = 10x -2 + 10x = 118 Solving -2 + 10x = 118 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 10x = 118 + 2 Combine like terms: -2 + 2 = 0 0 + 10x = 118 + 2 10x = 118 + 2 Combine like terms: 118 + 2 = 120 10x = 120 Divide each side by '10'. x = 12 Simplifying x = 12
| 8q^2+-10q+3=0 | | Y=-18+3x | | -9-2x=x+9 | | 2(2+4+w)= | | x+54+45+50+42+4x+8x=360 | | 3x-5=4x-12 | | -6x+8=-8+2x | | 2(x+3)=5(3x+4) | | 7v+1=29 | | 9a^2-24=-11a | | x-3=3-17 | | 4x+9-3x=0 | | 5x+139+9x+71+92=360 | | 2m+12=31 | | 9x+2x-8=4x-36 | | 2(x-3)+4(x-5)=0 | | 3x+7-9=4x+2 | | 6(y-3)-4=-2(-9y+8)-3y | | x+28=2x+29 | | (x+2)(x-7)(4x-3)=0 | | 4(8+6+z)=60 | | 3(4+6b)=25 | | (5x+5)=(7x+19) | | 9-3y=-12fory | | 2x+29=x+28 | | x^2-12X+C=Y | | a^2+5a=5a+4 | | 6b+9=122 | | Sec^2x-4secx=-4 | | 8t^2-5t-3=h | | -15=-7y+5(y-5) | | 5y-8=65 |